ABCA4 Mutation in a Patient With Juvenile Neuronal Ceroid Lipofuscinosis. (July 2017) - Reyes-Capó, Daniela; Ventura, Camila V.; Tekin, Mustafa; Lam, Byron L.; Berrocal, Audina M.
A 5-year-old Ecuadorian male, previously diagnosed with cone-rod dystrophy, presented for a second opinion after experiencing subjective bilateral rapid vision loss over an 18-day period, 4 months prior to consultation. Visual acuity was initially light perception in both eyes. Fundus examination revealed bilateral disc pallor, vascular attenuation, and retinal pigment epithelium atrophy. Electroretinogram showed minimal photopic response and no flicker nor scotopic responses in both eyes. At first, the patient demonstrated normal neurodevelopment. However, over the next 5 years, he developed severe neuromotor limitations and his vision progressed to no light perception in both eyes. Whole-exome sequencing detected CLN3 (p.Gly190Arg) and ABCA4 (p.Phe1026Leu) variant mutations. To the best of our knowledge, this is the first report describing a patient with simultaneous CLN3 and ABCA4 mutations, associated with juvenile Batten disease and inherited diseases of retinal degeneration, respectively.